Evaluating the global prevalence of insomnia during pregnancy through standardized questionnaires and diagnostic criteria: a systematic review and meta-analysis - Yang, Chengcheng; Fu, Rui; Wang, Huan; Jiang, Yanjie; Zhang, Shipeng; Ji, Xiaoli (Frontiers in Psychiatry, 2024)
Abstract: Insomnia during pregnancy presents significant medical care challenges and heightens the risk of adverse outcomes for both pregnant women and fetuses. This study undertook a meta-analysis to assess the global prevalence of insomnia during pregnancy, examining both the overall prevalence and regional variations. Method: The aim of this study was to perform a meta-analysis of articles indexed in PubMed, Embase, and Web of Science from the inception of these databases up to February 29, 2024. The study systematically reviewed the global prevalence of gestational insomnia and explored potential moderating factors, encompassing research type, publication date, regional influences, maternal age, pregnancy status, depressive symptoms, and anxiety symptoms. Result: Forty-four studies, encompassing a total of 47,399,513 participants, were included in the analysis. The overall prevalence of insomnia symptoms during pregnancy was 43.9%. Regional factors and depression emerged as the main factors affecting insomnia, with Europe (53.6%) surpassing North America (41.0%), followed by South America (50.6%) and Asia (40.7%). High depression rates (56.2%) correlated with increased insomnia prevalence compared to low depression rates (39.8%). The type of research and publication date showed no significant impact on the prevalence of insomnia symptoms. Conclusion: The meta-analysis results indicated that the prevalence of insomnia symptoms was higher during pregnancy, especially among pregnant women who were in a highly depressed state or located in the European region.